EFIKASI MINYAK ATSIRI TANAMAN CENGKEH (Syzygium aromaticum (L.) Meer. & Perry), PALA (Myristica fragrans Houtt), DAN JAHE (Zingiber officinale Rosc.) TERHADAP MORTALITAS ULAT BULU GEMPINIS DARI FAMILI LYMANTRIIDAE - Astuthi, Made Mika Mega; Sumiartha, Ketut; Susila, I Wayan; Wirya, Gusti Ngurah Alit Susanta; Sudiarta, I Putu (Journal of Agricultural Science and Biotechnology, 2012)
The analysis of efficacy of clove oil ( Syzigium aromaticum ), ginger oil ( Zingiber officinale ), and nutmeg oil ( Myristica fragrans ) to hairy caterpillar was conducted. The hairy caterpillar were reported to attack some plants in 2010 to 2011 in Indonesia .To control the caterpillar, recently, peoples used chemical insecticide, however the impact of chemicals insecticide is dangerous to human being, livestock, and environmental. Therefore to minimizing those problems, the control methods should be environmental-friendly and safe against human being. One of those methods is utilizing the botanical pesticide which is extracted from tropical plants. Therefore efficacy of essential oils was done in order to find out the method to control population of it with environmental friendly approach. The experiment result shown at the concentration 10%, all of the essential oils are effective to kill the caterpillar (90-100%). Therefore the examinations of low concentrations of essential oils were conducted (5, 2, and 1%). The result of 1% concentration of ginger oil, nutmeg oil and clove oil are 80 %, 76 % and 68 % respectively.
Keywords: Syzygium aromaticum; Myristica fragrans; Zingiber officinale; and hairy caterpilar